2015
DOI: 10.1057/jors.2014.129
|View full text |Cite
|
Sign up to set email alerts
|

A multiple criteria information system for pedagogical evaluation and professional development of teachers

Abstract: Information systems for the evaluation of pedagogical practices aim to improve teaching activity and encourage the pedagogical development of teachers. The implementation of these systems has been interpreted in different ways, depending on each school's administration board and/or the person responsible for the evaluation process. This ambiguity (and inherent subjectivity) is a barrier to the principles of transparency, equity and fairness in the pedagogical performance evaluation of teachers. From this premi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 49 publications
0
50
0
Order By: Relevance
“…Specifically, cognitive mapping allows evaluation criteria and their relationships to be revealed, while MACBETH facilitates the calculation of the respective trade-offs. Although both approaches have been previous applied and reported in the literature (see, for instance, Ferreira et al 2011;Canas et al 2015;Filipe et al 2015;Oliveira et al 2017), we have found no documented evidence reporting their combined use in the classification context of residential areas according to their exposure to crime.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Specifically, cognitive mapping allows evaluation criteria and their relationships to be revealed, while MACBETH facilitates the calculation of the respective trade-offs. Although both approaches have been previous applied and reported in the literature (see, for instance, Ferreira et al 2011;Canas et al 2015;Filipe et al 2015;Oliveira et al 2017), we have found no documented evidence reporting their combined use in the classification context of residential areas according to their exposure to crime.…”
Section: Introductionmentioning
confidence: 55%
“…This value tree will be operationalized, in a later stage of the structuring process, through the construction of descriptors (i.e. set of ordered performance levels) (see Filipe et al 2015;Gonçalves et al 2016). Next, the MAC-BETH approach will be applied, allowing the trade-offs between FPVs to be calculated, and local performance scales to be obtained for each descriptor.…”
Section: Methodological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of this concept has led us to the framework proposed in this paper, which has been successfully tested in other contexts (e.g. Ferreira 2011;Ferreira et al 2015;Filipe et al 2015), but which requires further applications involving different decision makers and different decision situations to ensure the potential and the generalization of the integrated use of these two approaches. It is in this testing stage that we have inserted this paper.…”
Section: Discussionmentioning
confidence: 99%
“…These are learning content and learning software evaluation problems (Kurilovas and Serikoviene, 2010), higher education decision making problems, (resource allocation, performance management, budgeting and scheduling) (Ho et al, 2006), using MCDA for accreditation in order to evaluate IT skills and qualifications (Siskosa et al, 2007), evaluating factors that determine the quality of higher education (Tsinidou et al, 2010), evaluation of the quality of e-learning systems (Tzenga et al, 2007) and educational websites (Shee and Wang, 2008), pedagogical evaluation of teachers (Filipe et al, 2015), evaluating quality of learning objects (Kurilovas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%